Mechanical properties and degradation behavior of binary magnesium-silver alloy sheets. (October 2019) - Liu, Zhidan; Feyerabend, Frank; Bohlen, Jan; Willumeit-Römer, Regine; Letzig, Dietmar
Abstract: The application of Mg–Ag alloys is suggested as biodegradable implant materials in the form of sheets with controllable mechanical properties and appropriate degradation behavior. This study aimed on the understanding of influence of rolling temperature and silver content (2–8 wt %) on the microstructure development, mechanical properties and the degradation behavior of the sheet material. Besides an increase of the average grain size with increasing rolling temperature, precipitates of Mg54 Ag17 formed during processing at lower temperatures and resulted in grain growth restriction during recrystallization. A typical alignment of basal planes parallel to the sheet plane was confirmed by texture measurements along with a strengthening of such textures when grains grew larger during recrystallization. As a result, an increase of the Ag-content corresponds to an increase in the hardness and strength properties of the sheets. In immersion tests, the as-rolled and annealed Q6 and Q8 rolled at 400 °C or 450 °C had similar degradation rate but an obvious difference of the degradation morphology due to the existence of precipitates at grain boundaries. By elevating the rolling and annealing temperature, the degradation rate decreased and the elimination of precipitates led to homogeneous degradation even when the silver in magnesium was up to 8 wt%. Appropriate short time annealing procedures below 60 s allow the tailored regulation of hardness, mechanical properties and ductility via controlled static recrystallization. Highlights: Thermo-mechanical treatment of Mg–Ag alloys leads to coarse grains by enhanced recrystallization and grain growth. Adjusted short time annealing allows tailored grain structure development with impact on the mechanical properties. A solid solution strengthening effect of Ag is maintained during rolling and annealing. Precipitation of Mg54 Ag17 increases the degradation rate and affects the morphology significantly.